2019
DOI: 10.1029/2018jd030240
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Mass Balance/4D‐Var Joint Inversion of NOx and SO2 Emissions in East Asia

Abstract: Accurate estimates of NOx and SO2 emissions are important for air quality modeling and management. To incorporate chemical interactions of the two species in emission estimates, we develop a joint hybrid inversion framework to estimate their emissions in China and India (2005–2012). Pseudo observation tests and posterior evaluation with surface measurements demonstrate that joint assimilation of SO2 and NO2 can provide more accurate constraints on emissions than single‐species inversions. This occurs through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 104 publications
(179 reference statements)
3
26
0
Order By: Relevance
“…These are related to the distribution of SO 2 sources over too few point sources in bottom-up inventories (Liu et al, 2018), lower SO 2 column densities in OMI retrievals compared to simulations, and small sources that are not detectable in OMI retrievals when the signal is comparable to the noise. The constraints from the prior emissions in the mass balance method (more details in Qu et al (2017) and Qu et al (2019) further limit the posterior emissions from deviating too much beyond the prior emissions, which were for 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are related to the distribution of SO 2 sources over too few point sources in bottom-up inventories (Liu et al, 2018), lower SO 2 column densities in OMI retrievals compared to simulations, and small sources that are not detectable in OMI retrievals when the signal is comparable to the noise. The constraints from the prior emissions in the mass balance method (more details in Qu et al (2017) and Qu et al (2019) further limit the posterior emissions from deviating too much beyond the prior emissions, which were for 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The global mean OH concentration in GEOS-Chem ranges from 10 × 10 15 to 13 × 10 15 molec/cm 3 from version 8 to version 12 (http://wiki.seas.harvard.edu/geos-chem/index.php/Mean_OH_concentration). Our subsequent study incorporates multiple species observations to synergistically change O 3 and OH concentration, and thus provide more accurate constraints on SO 2 emission estimates (Qu et al, 2019).…”
Section: 1029/2019jd030243mentioning
confidence: 99%
“…Our study here using OMPS thus touches an important issue, which is whether or not there would be any artificial trends in our climate data record of atmospheric SO2 and NO2 due to the transition of satellite sensors. Our study is also different from past studies (Wang et al, 2016;Qu et al, 2017;Qu et al, 2019a;Qu et al, 2019b) that have applied the 4D-Var technique to OMI data with the GEOS-Chem adjoint model, but did not include evaluation with independent satellite data. Qu et al (2019b) showed joint inversion using OMI SO2 and NO2 benefits from simultaneous adjustment of OH and O3 concentrations, which supports assimilating OMPS SO2 and NO2 observations simultaneously in this study.…”
mentioning
confidence: 72%
“…For example, satellite nitrogen dioxide (NO 2 ) columns have been used to constrain urban and shipping emissions of nitrogen oxides (NO x ; e.g., Huang et al, 2014;Vinken et al, 2014;Lu et al, 2015;Ding et al, 2018;Goldberg et al, 2019), namely, NO 2 and nitric oxide (NO), which are important contributors to secondary aerosol production in East Asian populated regions during warm seasons (e.g., Dong et al, 2014;Ge et al, 2013). However, satellite-observation-constrained emission estimates may be associated with variable levels of uncertainty depending on the emission inverse modeling approaches and the characteristics of the integrated satellite observations (e.g., Ding et al, 2017;Huang et al, 2014;Qu et al, 2019). It is therefore necessary to carefully evaluate the available satellite-observation-derived emissions, as well as their impacts on atmospheric conditions and atmosphere-biosphere interactions, for example, using stateof-the-art models and high-accuracy observations.…”
Section: Introductionmentioning
confidence: 99%